Limited Potential for Mineralization of Permafrost Peatland Soil Carbon Following Thermokarst: Evidence From Anoxic Incubation and Priming Experiments. Issue 12 (5th December 2022) - Estop‐Aragonés, Cristian; Heffernan, Liam; Knorr, Klaus‐Holger; Olefeldt, David
Abstract: Permafrost thaw in peatlands risks emitting vast stores of soil organic carbon (SOC) as greenhouse gases to the atmosphere, yet anoxic conditions and low peat quality may prevent rapid SOC loss. To assess differences in anaerobic SOC mineralization following thaw and vulnerability of previously‐frozen peat, we incubated peat (5° and 14°C) from 15 depths of ⁓6 m cores from different thaw sites including an intact permafrost peat plateau and thermokarst bogs that thawed ∼30 and ∼200 years ago. Furthermore, a glucose‐addition experiment after >700 days assessed whether labile C inputs occurring following thermokarst could accelerate SOC mineralization (priming). We found a common pattern of SOC mineralization rate decreasing with depth and peat age. However, we found no differences in peat mineralization rates among sites for samples of similar age and of corresponding peatland developmental stage. Priming effects were minor and short‐term, and did not vary among sites or with peat developmental stage. We also found mineralization rates from anoxic incubations more than an order of magnitude higher than rates implied from field observations, suggesting mineralization rates from anaerobic incubations should be used mainly to interpret relative differences. Peat humification and peat nitrogen and phosphorous content explained more than 85% of the variability in mineralization rates. Peat quality did not influence the temperature sensitivity of peat mineralization. Overall, the absence of substantial priming effects and the lack of differences in mineralization rates between permafrost peat and peat thawed 200 years ago suggests that rapid peatland SOC loss following thaw is unlikely. Plain Language Summary: Permafrost stores vast amounts of organic matter in peatlands. Ongoing permafrost thaw is exposing previously‐frozen peat to decomposition potentially releasing it as greenhouse gases but the magnitude of this release is uncertain. Following thaw, permafrost peatlands may turn into thermokarst bogs where soils are anoxic and waterlogged, which modifies vegetation. This vegetation and associated roots add easily decomposable substrates (labile) to deep soil layers, which could further increase peat decomposition. We did a two‐year incubation experiment to measure rates of peat decomposition from 15 depths of ⁓6 m cores from a permafrost peatland and thermokarst bogs that thawed 200 years ago. We also added glucose to assess the potential role of labile plant inputs on peat decomposition. We found that peat decomposition decreased with depth and peat age and this was reflected by the peat composition. However, when comparing samples of similar age, we did not find differences in decomposition rates between the permafrost peatland and the thermokarst bogs. The addition of glucose did not substantially stimulate decomposition either with no differences among sites. Overall, our results suggest limited loss of organic matter from previously‐frozen peat following thaw. Key Points: Similar peat decay rates in a thermokarst peatland than in a permafrost peatland suggests rapid organic matter loss after thaw is unlikely Organic matter humification indices combined with nutrient content explained more than 85% of the variability in peat decay rates Glucose addition did not result in sustained priming of permafrost peat and incubation‐based data overestimated in situ mineralization rates